2012
DOI: 10.3136/fstr.18.659
|View full text |Cite
|
Sign up to set email alerts
|

Elution Behavior Analysis of Starch Degrading Enzymes During Rice Cooking with Specific Antibodies

Abstract: Rice grains contain starch degrading enzymes, including α-glucosidases, α-amylases, β-amylases, pullulanase and isoamylases. To investigate the elution behavior of these enzymes from rice grains into cooking water during rice cooking, we separated cooking water from rice grains after soaking (20℃) and when the temperature reached 40℃ and 60℃ during cooking. Immunological detection of these enzymes in rice grains and cooking water was carried out with SDS-PAGE and immunoblot. Bands corresponding to pullulanase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In our previous studies, we revealed the distribution of starch-degrading enzymes in rice grains and their elution behavior during cooking with a specific antibody against each enzyme, including α-glucosidase, α-amylases, β-amylase, pullulanase and isoamylase, in Koshihikari cultivars (Tsuyukubo et al, 2010;Tsuyukubo et al, 2012). We also showed that starch hydrolytic activities and reducing sugar production differ with cooking temperature among Koshihikari, Nipponbare, Habutaemochi, Yumetoiro and Milkyqueen cultivars .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous studies, we revealed the distribution of starch-degrading enzymes in rice grains and their elution behavior during cooking with a specific antibody against each enzyme, including α-glucosidase, α-amylases, β-amylase, pullulanase and isoamylase, in Koshihikari cultivars (Tsuyukubo et al, 2010;Tsuyukubo et al, 2012). We also showed that starch hydrolytic activities and reducing sugar production differ with cooking temperature among Koshihikari, Nipponbare, Habutaemochi, Yumetoiro and Milkyqueen cultivars .…”
Section: Introductionmentioning
confidence: 99%
“…For this analysis, crude enzyme extracts from each fraction of raw rice grains, and those from cooking water were loaded as described previously (Tsuyukubo et al, 2012).…”
Section: -0%mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was shown that RNAi-mediated suppression of α-amylase genes in ripening seeds resulted in fewer chalky grains under high-temperature conditions, and the extent of the decrease in the ratio of chalky grains was highly correlated to decreases in the expression of Amy1A, Amy1C, Amy3A and Amy3B. 32) Furthermore, Tsuyukubo et al (2010Tsuyukubo et al ( , 2012 36,37) have demonstrated that AmyI-1 (Amy1A) and AmyII-4 (Amy3D) proteins existed in the outer layers (100 to 80% fractions) of rice grain (cv. Koshihikari), while α-glucosidase and AmyII-3 (Amy3E) were mainly detected in the inner layers (80 to 0% fractions) by immunoblotting with the specific antibodies.…”
Section: Breaking Test Of Cooked Rice Of Perfect and Chalky Grainsmentioning
confidence: 99%